profile
Опубликовано 1 год назад по предмету Алгебра от StageZ

1.Вычислите.

а)(√2)^(-2)-(√3)^(-2)
б)5,6+(-0,2)^(-3)
в)10^(-2)+0,1^(-2)

2.Представьте в виде дроби.
а)(x^2-y^2)^(-1)
б)(2x^(-2)+y^(-1)*x^(3)y

в)(2^(-3)+y^(3)*(2+y/2-y)^(-1)

  1. Ответ
    Ответ дан LFP

    a) (√2)^(-2)-(√3)^(-2) = 1 / (√2)^2 - 1 / (√3)^2 = 1/2 - 1/3 = 3/6 - 2/6 = 1/6

    б) 5,6+(-0,2)^(-3) = 5,6 + 1 / (-0,2)^3 = 5,6 - (10^3) / (2)^3 = 5,6 - 1000/8 = 5,6 - 125 = 119,4

    в) 10^(-2)+0,1^(-2) = 1/100 + 100 = 100,01

    а)(x^2-y^2)^(-1) = 1 / (x^2-y^2)

    б)(2x^(-2)+y^(-1)*x^(3)y = 2 / x^2 + x^3 = (2+x^5) / x^2

    в)(2^(-3)+y^(3)*(2+y/2-y)^(-1) = (16y^3 - y + 4) / (8(4-y))

Самые новые вопросы